Activity interference in patients with Sjögren's syndrome: a cross-sectional study of 149 patients in the UK. (30th January 2022) - Schoon, Hannah; Slack, Emma; Pearce, Mark; Ng, Wan-Fai; Hackett, Katie L
Abstract: Objectives: To investigate which five activity interference categories out of pain, fatigue, mood, dryness and brain fog/mental fatigue scored highest in patients with primary Sjögren's syndrome (pSS) and to investigate the association between activity interference and mood and physical functioning in these patients. Methods: The Comprehensive Pain Evaluation Questionnaire (CPEQ) assessed activity interference (actions performed in daily life that are hindered) in 149 UK pSS patients. This was modified to include four additional symptoms (fatigue, mood, dryness and brainfog/mental fatigue). Functional impairment was measured using the Hospital Anxiety and Depression Scale (HADS) and the Improved Health Assessment Questionnaire (Improved HAQ). Univariable linear regression models were estimated to investigate the association between CPEQ results and the outcome scores obtained from the HADS and Improved HAQ. Multivariable linear regression models were estimated adjusting for patient age and length of disease. Results: Fatigue had the biggest impact on seven activity domains: physical exercise (mean score of 3.49 out of 5 [s .d . 1.26]), performing household chores (mean 3.14 [s .d . 1.18]), gardening or shopping (mean 3.18 [s .d . 1.20]), socializing with others (mean 2.62 [s .d . 1.24]), recreation/hobbies (mean 2.88 [s .d . 1.20]), sexual relations (mean 3.00 [s .d . 1.52]), and mental efficacy (mean 2.69 [s .d . 1.17]). Regression analysis showed a positive correlation in which every point increase in an activity interference category saw the overall mood and physical functioning scores increase. Conclusion: Fatigue has the largest impact on pSS patients' daily activities in this cohort. Length of disease reduced the impact of activity interference on patients' overall health score.